1999
DOI: 10.1103/physrevlett.83.3776
|View full text |Cite
|
Sign up to set email alerts
|

Is SAX J1808.4-3658 a Strange Star?

Abstract: One of the most important questions in the study of compact objects is the nature of pulsars, including whether they are composed of β-stable nuclear matter or strange quark matter. Observations of the newly discovered millisecond X-ray pulsar SAX J1808.4-3658 with the Rossi X-Ray Timing Explorer place firm constraint on the radius of the compact star. Comparing the massradius relation of SAX J1808.4-3658 with the theoretical mass -radius relation for neutron stars and for strange stars, we find that a strange… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
242
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(259 citation statements)
references
References 44 publications
16
242
0
1
Order By: Relevance
“…Recent studies have shown that the compact objects associated with the transient X-ray burster SAX J1808.4-3658 (Li et al 1999a), the atoll X-ray source 4U 1728-34 (Li et al 1999b), the X-ray burster 4U 1820-30 (Bombaci 1997), the X-ray pulsar Her X-l (Dey et al 1998), and the hard X-ray burster GRO J1744-28 (Cheng et al 1998) are good strange star candidates. If the compact objects in these X-ray sources are really strange stars, then there will be very deep consequences for both astrophysics and the physics of strong interactions.…”
Section: Strange Star Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the compact objects associated with the transient X-ray burster SAX J1808.4-3658 (Li et al 1999a), the atoll X-ray source 4U 1728-34 (Li et al 1999b), the X-ray burster 4U 1820-30 (Bombaci 1997), the X-ray pulsar Her X-l (Dey et al 1998), and the hard X-ray burster GRO J1744-28 (Cheng et al 1998) are good strange star candidates. If the compact objects in these X-ray sources are really strange stars, then there will be very deep consequences for both astrophysics and the physics of strong interactions.…”
Section: Strange Star Candidatesmentioning
confidence: 99%
“…Using the observed X-ray luminosities, Li et al (1999a) derived a firm upper limit on the radius R of the compact object in SAX J 1808.4-3658 given by the dashed curve in the mass-radius (MR) plane in Fig. 1.…”
Section: Strange Star Candidatesmentioning
confidence: 99%
“…More speculative constraints on the radius have been proposed by Li et al (1999). Observations in 1998 of the accreting millisecond X-ray pulsar SAX J1808-3658 show pulsations at 401 Hz with a relatively steady pulse fraction and energy spectrum even as the flux from this source changed by a factor of ∼ 100.…”
mentioning
confidence: 99%
“…Observations in 1998 of the accreting millisecond X-ray pulsar SAX J1808-3658 show pulsations at 401 Hz with a relatively steady pulse fraction and energy spectrum even as the flux from this source changed by a factor of ∼ 100. Li et al (1999) then argue as follows. From the spin frequency we know the corotation radius R co for a given mass.…”
mentioning
confidence: 99%
“…This has not succeeded up to now, mainly because of uncertainties of the radii. Nevertheless, Li et al (1999) suggested that SAX J1808.4-3658 may be a quark star based on this relation and available data. Another constraint is the minimum mass of a pulsar or sub-millisecond pulsar.…”
Section: Introductionmentioning
confidence: 99%